Effect of carbon nanotubes support in improving the performance of mixed electrocatalysts for hydrogen evolution - Perica Paunović, Aleksandar T. Dimitrov, Orce Popovski, Dragan Slavkov and Svetomir Hadži Jordanov (Society of Chemists and Technologists of Macedonia, 2007)
The effect of using multiwalled carbon nanotubes (MWCNTs) vs. traditional carbon materials (as e.g., Vulcan XC-72) as supports for mixed non-platinum catalysts for hydrogen evolution was studied. Intrinsic changes in catalyst’s structure, surface and activity for hydrogen evolution were registered. It was found that MWCNTs significantly improve the activity of the catalysts as a result of (i) increase of the real surface area of the catalyst, (ii) improving the electrical conductivity of the electrode, (iii) better dispersion of active catalytic centers over the electrode surface and (iv) geometric nature of the nanotubes. This effect is most pronounced in the case of Ni-based catalyst, where the overpotential for hydrogen evolution was lowered by as much as 85 mV at a current density of 60 mA·cm-2 in alkaline electrolyte. The corresponding lowering of overpotential in the Co-based system was 35 mV.